Rotasi Kerja dan Kerjasama Tim : Pengaruhnya terhadap Kinerja Karyawan di PT PCM - Muhammad Alif Ghifari (Dharma Ekonomi, 2024)
Job rotation and teamwork are two important factors that can influence employee performance within an organization. This study aims to analyze the impact of job rotation and teamwork on employee performance at PT PCM. A quantitative approach was used in this study, employing a survey method involving a number of employees as respondents. Data were collected through questionnaires and analyzed using multiple linear regression to examine the relationship between the independent variables (job rotation and teamwork) and the dependent variable (employee performance). The results indicate that job rotation has a positive and significant effect on employee performance, as well-planned rotation can enhance employees' skills and flexibility. Additionally, teamwork also positively influences employee performance, as a collaborative work environment fosters effective communication and higher performance. These findings suggest that companies should implement strategic job rotation policies and strengthen a teamwork culture to improve overall employee performance.